Motivating Moral Behavior: Helping, Sharing, and Comforting in Young Children With Autism Spectrum Disorder - Dunfield, Kristen A.; Best, Laura J.; Kelley, Elizabeth A.; Kuhlmeier, Valerie A. (Frontiers in Psychology, 2019)
This exploratory study examined the role of social-cognitive development in the production of moral behavior. Specifically, we explored the propensity of children with Autism Spectrum Disorders (ASD) to engage in helping, sharing, and comforting acts, addressing two specific questions: (1) Compared to their typically developing (TD) peers, how do young children with ASD perform on three prosocial tasks that require the recognition of different kinds of need (instrumental, material, and emotional), and (2) are children with ASD adept at distinguishing situations in which an adult needs assistance from perceptually similar situations in which the need is absent? Children with ASD demonstrated low levels of helping and sharing but provided comfort at levels consistent with their TD peers. Children with ASD also tended to differentiate situations where a need was present from situations in which it was absent. Together, these results provided an initial demonstration that young children with ASD have the ability to take another’s perspective and represent their internal need states. However, when the cost of engaging in prosocial behavior is high (e.g., helping and sharing), children with ASD may be less inclined to engage in the behavior, suggesting that both the capacity to recognize another’s need and the motivation to act on behalf of another appear to play important roles in the production of prosocial behavior. Further, differential responding on the helping, sharing, and comforting tasks lend support to current proposals that the domain of moral behavior is comprised of a variety of distinct subtypes of prosocial behavior.